Formation and evolution of fracture spacing on various geometric surfaces in layered materials. (15th December 2021) - Ma, T.H.; Zhu, X.; Tang, C.A.; Li, W.R.
Abstract: Fracture spacing as a widespread phenomenon in nature shows similar patterns on various geometric surfaces. To explore the similarities and differences between various geometric surfaces in the process of fracture spacing formation, numerical simulations are conducted on bi-layered three-dimensional models of three various geometric surfaces, including slab surface, cylindrical surface, and spherical surface by the finite element method (FEM). The fractures develop under a quasi-static loading condition with constant displacement increments. The progressive failure process from fracture initiation to saturation is researched, and the material heterogeneity is introduced by using a probability distribution, which acts as the main reason for failures generating randomly inception. An intuitive explanation is also provided for the phenomenon of fracture saturation. Then, as the loading condition varies, fracture patterns in both slab surface models and cylindrical surface models show a transition from parallel fractures, step-like fractures to regular polygonal fractures. However, in spherical surface models, only uniform polygonal fractures emerge under the condition of radial expansion. Furthermore, through quantitative analysis by statistical means, we find that, except for the fractured layer thickness, curvature also has a significant impact on the crack density.